Projekt wdrożenia zintegrowanego systemy informatycznego mySAP ERP na przykładzie centrum logistycznego - Kiba-Janiak, Maja (Project of Implementing the Integrated Computerized Information System MySAP ERP on Example of Logistic Centre, 2008)
The article presents the project of implementing the integrated computerized information mySAP ERP system on an example of logistic centre. The first part of this article shows the preparation process of implementing IT system in a company. The author also defines the term of integrated computerized information system. The second part of this paper describes the mySAP ERP system. Furthermore, the author presents the stages and methods of implementing the integrated computerized information mySAP ERP system on the example of a logistic centre.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 11, s. 282-291